Influenza A viruses remain infectious for more than seven months in northern wetlands of North America. Issue 1934 (9th September 2020) - Ramey, Andrew M.; Reeves, Andrew B.; Drexler, Judith Z.; Ackerman, Joshua T.; De La Cruz, Susan; Lang, Andrew S.; Leyson, Christina; Link, Paul; Prosser, Diann J.; Robertson, Gregory J.; Wight, Jordan; Youk, Sungsu; et al.
Abstract : In this investigation, we used a combination of field- and laboratory-based approaches to assess if influenza A viruses (IAVs) shed by ducks could remain viable for extended periods in surface water within three wetland complexes of North America. In a field experiment, replicate filtered surface water samples inoculated with duck swabs were tested for IAVs upon collection and again after an overwintering period of approximately 6–7 months. Numerous IAVs were molecularly detected and isolated from these samples, including replicates maintained at wetland field sites in Alaska and Minnesota for 181–229 days. In a parallel laboratory experiment, we attempted to culture IAVs from filtered surface water samples inoculated with duck swabs from Minnesota each month during September 2018–April 2019 and found monthly declines in viral viability. In an experimental challenge study, we found that IAVs maintained in filtered surface water within wetlands of Alaska and Minnesota for 214 and 226 days, respectively, were infectious in a mallard model. Collectively, our results support surface waters of northern wetlands as a biologically important medium in which IAVs may be both transmitted and maintained, potentially serving as an environmental reservoir for infectious IAVs during the overwintering period of migratory birds.